Fungal effector protein AVR2 targets diversifying defense-related cys proteases of tomato. - Shabab, M; Shindo, T; Gu, C; Kaschani, F; Pansuriya, T; Chintha, R; Harzen, A; Colby, T; Kamoun, S; van der Hoorn, R (2008)
The interaction between the fungal pathogen Cladosporium fulvum and its host tomato (Solanum lycopersicum) is an ideal model to study suppression of extracellular host defenses by pathogens. Secretion of protease inhibitor AVR2 by C. fulvum during infection suggests that tomato papain-like cysteine proteases (PLCPs) are part of the tomato defense response. We show that the tomato apoplast contains a remarkable diversity of PLCP activities with seven PLCPs that fall into four different subfamilies. Of these PLCPs, transcription of only PIP1 and RCR3 is induced by treatment with benzothiadiazole, which triggers the salicylic acid-regulated defense pathway. Sequencing of PLCP alleles of tomato relatives revealed that only PIP1 and RCR3 are under strong diversifying selection, resulting in variant residues around the substrate binding groove. The doubled number of variant residues in RCR3 suggests that RCR3 is under additional adaptive selection, probably to prevent autoimmune responses. AVR2 selectively inhibits only PIP1 and RCR3, and one of the naturally occurring variant residues in RCR3 affects AVR2 inhibition. The higher accumulation of PIP1 protein levels compared with RCR3 indicates that PIP1 might be the real virulence target of AVR2 and that RCR3 acts as a decoy for AVR2 perception in plants carrying the Cf-2 resistance gene.